Cisplatin induces autophagy to enhance hepatitis B virus replication via activation of ROS/JNK and inhibition of the Akt/mTOR pathway - Chen, Xuemei; Hu, Yuan; Zhang, Wenlu; Chen, Ke; Hu, Jie; Li, Xiaosong; Liang, Li; Cai, Xuefei; Hu, Jieli; Wang, Kai; Huang, Ailong; Tang, Ni (Free radical biology & medicine, 2019)
Chronic hepatitis B virus (HBV) infection remains a serious global health concern. Cisplatin is a chemotherapeutic agent commonly used to treat various cancers. However, HBV-infected patients receiving chemotherapy are at risk of HBV reactivation via unknown mechanisms, which we aimed to elucidate in this study. We found that autophagy plays a central role in cisplatin-induced HBV replication. Cisplatin treatment induced autophagy in both HBV-replicating cells and an HBV-transgenic mouse model as evident from marked upregulation of microtubule-associated protein 1 light chain 3 (LC3)-II and the accumulation of red fluorescent protein (RFP)-LC3 puncta. Cisplatin induced complete autophagic flux, which was detected via monitoring of p62 degradation and RFP-GFP-LC3 expression. Inhibition of autophagy by chloroquine, 3-methyladenine, or Atg5 knockdown significantly attenuated cisplatin-induced HBV replication. Additionally, cisplatin-induced autophagy could be significantly attenuated by using the ROS scavenger N-acetyl-l-cysteine. Mechanically, cisplatin promoted HBV replication and autophagy through ROS/JNK and AKT/mTOR signaling. Inhibition of JNK or activation of Akt/mTOR signaling reversed cisplatin-mediated autophagy and HBV replication promotion. In contrast, suppression of Akt/mTOR signaling further promoted cisplatin-induced HBV replication. Finally, pharmacotherapeutic inhibition of autophagy or ROS production impaired HBV production induced by cisplatin in vivo. Together, our results indicate that ROS/JNK and mTOR/AKT-mediated autophagy plays an important role in cisplatin-induced HBV reactivation. [Display omitted] •Cisplatin stimulates HBV replication in vitro and in vivo.•Cisplatin induces autophagy to enhance hepatitis B virus replication.•Inhibition of autophagy or ROS/JNK axis rendered cisplatin-induced HBV biosynthesis.•Cisplatin promotes HBV replication and autophagy by ROS/JNK and AKT/mTOR pathway.